KARAKTERISTIK PELINGKUP JALAN MARGA UTAMA KOTA YOGYAKARTA - Annisa Nursita Rohmah; Ahmad Sarwadi (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
This research was conducted to determine the physical characteristics of the scope of Marga Utama Street in Yogyakarta. Not only as a concentration of views, but the road is also part of the city's philosophical axis. The preparation of this research is supported by relevant literacy and regulatory standards set by the Government. The research method used is qualitative rationalism, field data collection based on theoretical studies and predetermined variables. The result of this study is in the form of a scoping direction concept which implies the scoping characteristics of Marga Utama Street. This is because the current road conditions do not reflect the philosophical axis of the city of Yogyakarta. Several factors that affect the scoping characteristics along Marga Utama Street are building height, building setback, architectural pattern, signage, and street trees.